Eley–Rideal model of heterogeneous catalytic carbamate formation based on CO2–MEA absorptions with CaCO3, MgCO3 and BaCO3. Issue 5 (1st May 2019) - Shi, Huancong; Huang, Min; Huang, Yuandong; Cui, Lifeng; Zheng, Linna; Cui, Mingqi; Jiang, Linhua; Ibrahim, Hussameldin; Tontiwachwuthikul, Paitoon
Abstract : The mechanism was proposed of heterogeneous catalytic CO2 absorptions with primary/secondary amines involving 'catalytic carbamate formation'. Compared with the non-catalytic 'Zwitterion mechanism', this Eley–Rideal model was proposed for CO2 + RR′NH with MCO3 (M = Ca, Mg, and Ba) with four elementary reaction steps: (B1) amine adsorption, (B2) Zwitterion formation, (B3) carbamate formation, and (B4) carbamate desorption. The rate law if determining step of each elementary step was generated based on 'steady-state approximation'. Furthermore, the solid chemicals were characterized by SEM and BET, and this rate model was verified with 39 sets of experimental datasets of catalytic CO2 –MEA absorptions with the existence of 0–25 g CaCO3, MgCO3 and BaCO3 . The results indicated that the rate-determining step was B1 as amine adsorption onto solid surface, which was pseudo-first-order for MEA. This was the first time that the Eley–Rideal model had been adopted onto the reactions of CO2 + primary/secondary amines over alkaline earth metal carbonate (MCO3 ).